MEMPREDIKSI RETURN SAHAM: KEAKURATAN 2 (DUA) MODEL FAMA FRENCH DAN CAPM - Yunan Surono (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2016)
In the world of investment, there is a lot of model being used to calculate a return which will be compared with the available risk. The model that being compared in this investigation is the capital asset pricing model and the Fama French three factor model. The Capital Asset Pricing model is one of the model that calculate return using the market risk factor only, while the fama French three factor model uses the factor of market risk, size and book to market equity.The investigation uses 12 data of stock market companies that have been chosen from 45 companies’ data. This data have met the requirement in the investigation. The period of the data is taken from 2005 until 2015. Every data will be processed based on several portfolios and the result will be entered to both of the model to calculate the return estimation. Each of this return estimation will be compared to know the accuracy to calculate the return. With this comparison then investor able to evaluate which model to be used in the situation and condition at the present.Keyword: Fama-French Three Factor Model, Capital Asset Pricing Model, Investment